Characterization of a novel binding site for the human immunodeficiency virus type 1 envelope protein gp120 on human fetal astrocytes. - Ma, M (1994)
125I-labeled recombinant gp120 bound to primary cultures of human fetal astrocytes with a single class of 260-kDa binding sites, with a Kd of 26 nM and maximal number of binding sites of 29.9 fmol/4 x 10(4) cells. Neither CD4 nor galactocerebroside was detectable on astrocytes, and 125I-labeled recombinant gp120 binding to astrocytes was not blocked by antibodies against galactocerebroside or the gp120 binding domain of CD4.